Resonance‐stabilized partial proton transfer in hydrogen bonds of incommensurate phenazine–chloranilic acid. Issue 2 (1st April 2015) - Noohinejad, Leila; Mondal, Swastik; Ali, Sk Imran; Dey, Somnath; van Smaalen, Sander; Schönleber, Andreas
<x xml:space="preserve">Abstract</x> The co‐crystal of phenazine (Phz) and chloranilic acid (H2ca) becomes ferroelectric upon cooling through the loss of inversion symmetry. Further cooling results in the development of an incommensurate ferroelectric phase, followed by a lock‐in transition towards a twofold superstructure. Here we present the incommensurately modulated crystal structure of Phz‐H2ca at T = 139 K with a symmetry given by the superspace group P21(½σ2½)0 and σ2 = 0.5139. The modulation mainly affects the positions of the protons within half of the intermolecular hydrogen bonds that are responsible for the spontaneous polarization in all three low‐temperature phases. Evidence for proton transfer in part of the hydrogen bonds is obtained from the correlated dependence on the phase of the modulation of the lengths of bonds involved in resonance stabilization of the acidic anion, and much smaller variations of bond lengths of atoms not involved in the resonance mechanism. Incommensurability is explained as competition between proton transfer favored for single hydrogen bonds on the basis of pKa values and avoiding unfavorable Coulomb repulsion within the lattice of the resulting ionic molecules.